2001
DOI: 10.1055/s-2001-16579-1
|View full text |Cite
|
Sign up to set email alerts
|

Intrakoronare, humane autologe Stammzelltransplantation zur Myokardregeneration nach Herzinfarkt

Abstract: These results for the first time demonstrate that selective intracoronary transplantation of human autologous adult stem cells is possible under clinical conditions and that it can lead to regeneration of the myocardial scar after transmural infarction. The therapeutic effects may be ascribed to stem cell-associated myocardial regeneration and neovascularisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(49 citation statements)
references
References 0 publications
0
44
0
5
Order By: Relevance
“…9 In clinical myocardial infarction, evidence has been provided that autologous bone marrow stem cells may regenerate in infarcted myocardium and improve myocardial perfusion of the infarct zone. 3 Studies with transplanted human hearts have shown that adult humans have extracardiac progenitor cells capable of migrating to and repopulating damaged myocardium, a process occurring at very low levels. 10 Recently, cases have been described in which a male patient receives a heart from a female donor, which provided an opportunity to test whether progenitor cells translocate from the recipient to the graft on the basis of Y chromosome labeling.…”
Section: Stem Cell Differentiation To Muscle Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 In clinical myocardial infarction, evidence has been provided that autologous bone marrow stem cells may regenerate in infarcted myocardium and improve myocardial perfusion of the infarct zone. 3 Studies with transplanted human hearts have shown that adult humans have extracardiac progenitor cells capable of migrating to and repopulating damaged myocardium, a process occurring at very low levels. 10 Recently, cases have been described in which a male patient receives a heart from a female donor, which provided an opportunity to test whether progenitor cells translocate from the recipient to the graft on the basis of Y chromosome labeling.…”
Section: Stem Cell Differentiation To Muscle Cellsmentioning
confidence: 99%
“…3 Except for hematopoietic and mesenchymal stem cells, many other bone marrow-related cell types may participate in organ repair of infarction models; bone marrow hemangioblasts take part in neovascularization, mesodermal progenitor cells are contained within the mononuclear bone marrow cell fraction that differentiates to endothelial cells, and endothelial progenitor cells can transdifferentiate into cardiomyocytes. Primitive bone marrow cells mobilized by stem cell factor and granulocyte-colony stimulating factor are capable of homing to infarct regions, replicating, differentiating, and promoting myocardial repair.…”
Section: Stem Cellsmentioning
confidence: 99%
“…In 2001, first encouraging pre-clinical study results, reporting the repair of infarcted cardiac tissue and the enhancement of ventricular function, led to the rapid translation of SC therapies within the same year [4][5][6]. Over the last two decades, plenty of preclinical and early clinical trials have demonstrated the safety and feasibility of numerous SC types.…”
Section: Introductionmentioning
confidence: 99%
“…These types of cells exist in mature tissues and can generate different cell types and even regenerate organs. Currently, there are no ethical restrictions on adult stem cells and it was recently shown that autologous adult stem cells have shown therapeutic prevalence in heart disease treatment and other diseases (3)(4)(5)(6). The main areas of general medicine, (except onco-hematology, cancer, and systemic diseases), where treatment with stem cell became in common use are depicted in Figure 1.…”
mentioning
confidence: 99%
“…Besides, there are no currently available reports showing the optimal dosage and route of administration of stem cells neither in human nor in animal models. Nevertheless, the most common route of interventions conducted via intraarterial or intravenous infusions to provide systemic delivery to damaged organs/tissues and via local applications for treatment of local external surgical diseases such as burns, ulcers, and wounds (3,6,18,23).…”
mentioning
confidence: 99%